Kognitivni in družbenoekonomski dejavniki šolskega uspeha v Sloveniji - Klanjšek, Rudi (Družboslovne razprave, 2007)
The conditionality of academic performance, seen as one of the main pillars of the stratification structure of contemporary society, which includes the relationship between natural, descent-based and socio-cultural factors has been the subject of long debate. Sociological thought has consistently accentuated the role of social and cultural factors in one's educational, occupational and other attainments. A number of non-sociological authors have questioned the perception of such societal determinism. This paper tested the impact of various factors, including one used as an indicator of what is usually called 'mental ability' (or intelligence), on children's academic achievement on a sample of 1,156 Slovenian secondary school pupils. The results did not warrant a definite conclusion about the predominance of either cognitive or environmental influences, but indicated that the score one achieved in the mental ability test was a significant explanatory variable. Other significant factors included the education of one's mother (which was more influential than the father's) and gender.
Keywords: Družbena neenakost; Social inequality; Šolanje; Schooling; Secondary school students; Srednješolci; Successfulness; Uspešnost; Socioeconomic status; Družbenoekonomski položaj; Kulturni kapital; Cultural capital; Socializacija; Socialization; Sposobnost; Ability; Slovenia; Slovenija; šolska uspešnost